"The Role Of Pedagogy In The Education Of Personality" - Zakir Avliyakulov; Khamidova Rushana (Genius Journals, 2025)
The article analyzes the importance and role of pedagogy in the education of personality. Pedagogy is one of the main sciences that influences the spiritual, moral and intellectual development of a person. Its principles, methods and approaches play an important role in the process of education. The study examines the main areas of education, pedagogical approaches and their results. It also examines modern problems of education and upbringing, as well as ways to solve them. The article can be useful for teachers, parents and specialists in the field of education.
Keywords: pedagogy in the education; spiritual; moral and intellectual development of a person